Observation of Dynamic Cellular Migration of the Medial Edge Epithelium of the Palatal Shelf in vitro - Aoyama, Gozo; Kurosaka, Hiroshi; Oka, Ayaka; Nakatsugawa, Kohei; Yamamoto, Sayuri; Sarper, Safiye Esra; Usami, Yu; Toyosawa, Satoru; Inubushi, Toshihiro; Isogai, Yukako; Yamashiro, Takashi (Frontiers in Physiology, 2019)
Palatal fusion is a critical step during palatogenesis. In this fusing interface, the epithelial sheets need to be removed in order to achieve mesenchymal continuity. Epithelial cellular migration is one of the possible mechanisms, and live imaging of the labeled epithelium could provide direct evidence for it. However, the removal of medial edge epithelium (MEE) between the bilateral processes takes place in the middle of the dorso-ventral axis of the palatal shelf, and thus it is challenging to capture the cellular behavior directly. Here, we evaluate cellular behavior of MEE cells using a live imaging technique with a mouse model which expresses GFP under the promoter of Keratin14 (K14-GFP) and unpaired palatal shelf culture. Using this approach, we successfully obtained live images of epithelial behavior and detected epithelial cell autonomous migration on the surface of the secondary palatal shelf without touching of the opposing shelf. Additionally, the pattern of epithelial elimination resulted in oval-shaped exposed mesenchyme, which recapitulated the situation during secondary palate fusion in vivo. Detailed image processing revealed that most of the MEE migrated in an outward direction at the boundary regions as the oval shape of the exposed mesenchyme expanded. The migration was preceded by the bulging of MEE, and disappearance of GFP signals was not evident in bulging or migrating MEE at the boundary regions. Furthermore, the MEE migration and the subsequent mesenchymal exposure were disturbed by application of ROCK inhibitor. Together, these findings indicated that epithelial cell migration contributed importantly to the MEE removal and the subsequent exposure of the underlying mesenchyme. Furthermore, they indicated that the migration of epithelial cells was autonomously regulated in a time- and space-specific manner, since unpaired palatal shelf culture exhibited these cellular behaviors even in the absence of the opposing shelf. Altogether, present data indicated that this new experimental system combining live imaging with GFP-labeled epithelium mice and unpaired palatal shelf culture enabled direct visualization of cellular migration of MEE in vitro and could be a powerful tool to investigate its cellular and molecular mechanisms.